Using of Play Store as a Media for Disseminating Hadith and other forms of Hadith Studies on the Play Store - Rosa, Elis Mila (Program Studi Ilmu Hadis Fakultas Ushuluddin Adab dan Dakwah IAIN Langsa, 2022)
In the era of revolution 5.0, advances in technology and information brought significant changes. From these changes, it is able to affect the system of everything related to humans such as in social, economic, political, educational and other life. The use of the play store as a medium and method of application in the learning process is a form of technology contribution to assist the education system. For example, the media for the dissemination of scientific studies, especially in the field of hadith, can be found in applications available on the play store. The study of hadith currently includes a lot of hadith historiography, the history of codification in the previous era and only a few studies that specifically discuss the development of hadith using the internet, especially in the realm of distributing hadith in the play store. In the past, the form of hadith can only be studied in the original print, it is different from now it can be seen in non-printed form such as applications. Of the many hadith applications available on the play store, the author takes three hadith applications, namely the hadith encyclopedic application of the book of 9 imams, children's hadith and hadith bushes. This study wants to show that hadith learning can be done other than through the original book and the three applications above are real evidence that hadith can be accessed easily through the play store with the help of the internet. This research is a type of qualitative research that has a descriptive nature and tends to use analysis. The results of this study indicate that the distribution of hadith in the play store has an influence on users in studying hadith. Then, the three hadith applications in the play store provide a new learning space for users to make it easier to solve the problems to be solved.